2019
DOI: 10.1093/trstmh/trz117
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and associated risk factors of toxocariasis among nomads in Boyer-Ahmad County, southwest Iran

Abstract: Background Human toxocariasis is caused by the larval stage of Toxocara canis and Toxocara cati. This cross-sectional study was conducted to evaluate the seroprevalence and the risk factors associated with Toxocara infection in nomads of Boyer-Ahmad County in the southwest of Iran. Methods A total of 968 blood samples were collected from nomads. A structured questionnaire, containing sociodemographic data, was completed for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…Moreover, the results of a meta-analysis study in Iran reported the rates of 0.84 to 29% for the seroprevalence of human toxocariasis in different areas of the country [ 8 ]. Despite several studies conducted in different parts of the country, studies conducted on high-risk groups in Iran are few [ 9 11 ]. Undoubtedly, one of these high-risk groups is the mentally retarded patients, who are mostly maintained in institutions with inadequate health facilities which increases their chances of getting infectious diseases including Toxocara infection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results of a meta-analysis study in Iran reported the rates of 0.84 to 29% for the seroprevalence of human toxocariasis in different areas of the country [ 8 ]. Despite several studies conducted in different parts of the country, studies conducted on high-risk groups in Iran are few [ 9 11 ]. Undoubtedly, one of these high-risk groups is the mentally retarded patients, who are mostly maintained in institutions with inadequate health facilities which increases their chances of getting infectious diseases including Toxocara infection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…About a 3 mL, venous blood sample was collected from all participants in both groups. The serum was separated and tested for IgG anti- Toxocara antibodies by ELISA method using the T. canis larval excretory-secretory (E/S) antigens prepared using the method previously described ( 22 ). For the ELISA method, flat-bottom 96-well microplate (corning, USA) was coated with 5 μg/mL of Toxocara E/S antigen overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Trichinosis is a zoonotic disease caused by Trichinella spiralis, a parasite of the genus Trichinellaceae. Besides humans, animals including pigs, dogs, cats, rodents and wild boars can be infected with this parasite (Arefkhah et al 2020). Trichinella spiralis is a common pathogen that causes human diseases and can cause infection after eating raw or undercooked meat containing Trichinella spiralis larvae (Dimzas et al 2019).…”
Section: Trichinosismentioning
confidence: 99%